Assessment of crashworthiness of the frontal part of a local car model - Nimir, Yassin Lutfi Mahmud; Abdullah, Kassim Abdulrahman; Lon, Wong Lek (Inderscience Enterprises Ltd., 2014)
For an integral body or a body-on-frame vehicle, the vehicle’s frontal part is the major structural subsystem to absorb the impact energy in a frontal vehicle impact. Ideally, for each serious crash situation, the whole available deformation length must be used and all the impact energy must be absorbed without deforming the passenger compartment. It is also important to manage the intensity during the crash time because the resulting crash pulse has a large influence on the injury level. Crash simulation software is widely used by the automotive industry to evaluate occupant risks and injuries. Therefore, the accuracy of the finite element frame model has significant influence on the quality of vehicle impact predictability. This work aims at building an understanding of structural and design features that can optimise structural integrity in terms of strength, stiffness and crashworthiness of front-part structures. For this, a local car model is selected for analysis so as to study and analyse the crushing behaviour and suggest ways for possible modifications to be made on the structures at the weak zones to enhance crashworthiness of the vehicle